Aquatic heterotrophic bacteria have highly flexible phosphorus content and biomass stoichiometry - Godwin, Casey M (ISME J, 2015)
Bacteria are central to the cycling of carbon (C), nitrogen (N) and phosphorus (P) in every ecosystem, yet our understanding of how tightly these cycles are coupled to bacterial biomass composition is based upon data from only a few species. Bacteria are commonly assumed to have high P content, low biomass C:P and N:P ratios, and inflexible stoichiometry. Here, we show that bacterial assemblages from lakes exhibit unprecedented flexibility in their P content (3% to less than 0.01% of dry mass) and stoichiometry (C:N:P of 28: 7: 1 to more than 8500: 1200: 1). The flexibility in C:P and N:P stoichiometry was greater than any species or assemblage, including terrestrial and aquatic autotrophs, and suggests a highly dynamic role for bacteria in coupling multiple element cycles.